2012
DOI: 10.5194/isprsarchives-xxxviii-1-c22-81-2011
|View full text |Cite
|
Sign up to set email alerts
|

Aerial Magnetic Sensing With an Uav Helicopter

Abstract: This paper concentrates on aerial magnetic sensing with an autonomous Scout B1-100 UAV helicopter. A high-resolution 3-axis magnetic sensor has been mounted on the helicopter in order to generate a detailed magnetic map and to identify various ferrous objects in the soil. The development is based on advanced mission planning for the UAV as well as test flights under challenging weather conditions such as wind gusts and snow fall. Finally, this paper summarizes a real-world application after the collapse of a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…The field experiment showed that the UAV magnetic measurement system was able to clearly delineate the mineralization with finer sampling, higher resolution over the conventional aeromagnetic survey. Christoph Eck and Benedikt Imbachy [17] designed an aerial magnetic sensing scheme with the Scout B1-100 UAV helicopter and a three-axis magnetic sensor, which was applied in the humanitarian rescue. In [18], two Geometrics G-823A cesium vapor magnetometers, a computer, power supplies, differential GPS, IMU, and fluxgate magnetometer are mounted on the fixed-wing UAV, called Venturer, for the aeromagnetic surveying.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The field experiment showed that the UAV magnetic measurement system was able to clearly delineate the mineralization with finer sampling, higher resolution over the conventional aeromagnetic survey. Christoph Eck and Benedikt Imbachy [17] designed an aerial magnetic sensing scheme with the Scout B1-100 UAV helicopter and a three-axis magnetic sensor, which was applied in the humanitarian rescue. In [18], two Geometrics G-823A cesium vapor magnetometers, a computer, power supplies, differential GPS, IMU, and fluxgate magnetometer are mounted on the fixed-wing UAV, called Venturer, for the aeromagnetic surveying.…”
Section: Introductionmentioning
confidence: 99%
“…To date, considerable progress has been made in the integration and testing of the UAV-magnetometer system. Whether it is based on the fixed-wing UAV [17,18] or multi-rotor UAV [15,16,19], a single magnetometer [15][16][17] or multiple magnetometers [18], the UAV-magnetometer system shows excellent performance over the handheld and aeromagnetic devices. However, the research on the processing and interpretation of UAV magnetic data is quite rare and challenging because of the low quality of magnetic data and the lack of interpretation methods for the UAV-based magnetic survey.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unmanned aircraft systems (UAS) are increasingly used for small‐scale (<10 km 2 ) high‐resolution magnetic surveys in part because they offer reduced mobilization time and operating costs compared to traditional manned airborne surveys (Funaki and Hirasawa ; Eck and Imbach ; Koyama et al . ; Hashimoto et al .…”
Section: Introductionmentioning
confidence: 99%
“…Gold has information for prospection works [27][28][29]. Other airborne sensors, such as magnetic, have also extensively contributed to a more detailed surveying of ore deposits and structural analysis [30].…”
Section: Introductionmentioning
confidence: 99%